Stimulasi Denyut Jantung dengan Pemutar Musik pada Android - Afandi, Ifan Kurnia; Ferdiana, Ridi; Nugroho, Hanung Adi (Universitas Diponegoro, 2014)
Music is a natural instrument that can be enter in every human life. Music used by the ancestors in traditional ceremonies and partly uses music to inspire the spirit of fighting on a war or on a sports competition. Music is also used by some people for relaxation. Music tempo affects heart rate in a unique way. Fast music tempo will increase the heart rate. Instead slow music tempo that tends to be used for relaxation. Today the daily activities can not be separated from smartphones and music. This paper presents a unique approach to increase the heart rate. Simple application become the base of application so that application can be use easily. Increased heart rate can be a support to maximize daily activities. Keywords: Heart rate; Music; Smartphone